PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN NORMA SUBJEKTIF TERHADAP MINAT MEMILIH PERGURUAN TINGGI STIE TAMANSISWA BANJARNEGARA DENGAN SIKAP SEBAGAI VARIABEL INTERVENING - Ratna Suryani; Ghonimah Zamroatun Ainiyah (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2021)
This study aimed to determine how much intention in choosing STIE Tamansiswa Banjarnegara Higher Education influenced by kualitas produk, price perceptions, and subjective norms through attitude as an intervening variable. Triggered by the phenomenon of the number of new student registrants at STIE Tamansiswa Banjarnegara which have never reached ten percent of the total number of all SMA/SMK/MA alumni in Banjarnegara each year. Refers to the model of Theory Reasoned-Action developed by Fishbein-Ajzen, behavioral intentions are a function of attitude toward behavior and the subjective norm. This type of research isquantitative research using primary data derived from questionnaire instruments and given to one hundred respondents. The sampling technique in this study was purposivesampling by determining certain criteria on the sample to be studied. Based on the results obtained, it shows that product quality and price perception can influence the intention in choosing college with attitude as an intervening variable. While attitudes have a positive influence on interest in choosing college. But this is different with subjective norms which have a negative influence on the intention in choosing college.From these results it can be concluded that the proposed reasoned-actioned theory is proven that the intention in choosing college is influenced by the attitudes andsubjective norms of each individu.